Social Cognition in Children With Non-specific Intellectual Disabilities: An Exploratory Study - Jacobs, Emilie; Simon, Poline; Nader-Grosbois, Nathalie (Frontiers in Psychology, 2020)
Social cognition abilities, notably Theory of Mind (ToM) and Social information processing (SIP), are key skills for the development of social competences and adjustment. By understanding affective and cognitive mental states and processing social information correctly, children will be able to enact prosocial behaviors, to interact with peers and adults adaptively and to be socially included. As social adjustment and inclusion are major issues for children with intellectual disabilities (IDs), the present study aimed to explore their social cognition profile by combining cluster analysis of both ToM and SIP competences, and to investigate the structure of relations between these skills in children with IDs. Seventy-eight elementary school children with non-specific IDs were recruited. They had a chronological age ranging from 4 years and 8 months to 12 years and 6 months and presented a preschool developmental age. Performance-based measures were administered to assess ToM and SIP abilities. Questionnaires were completed by the children’s parents to evaluate the children’s social competences and adjustment and their risk of developing externalizing or internalizing behaviors. Exploratory analysis highlighted strengths and weaknesses in the social cognition profiles of these children with IDs. It also emphasized that the understanding of affective and cognitive mental states was used differently when facing appropriate vs. inappropriate social behaviors. The present study leads to a better understanding of the socio-emotional profile of children with IDs and offers some suggestions on how to implement effective interventions.